APPLICATION OF AUGMENTED REALITY IN E-COMMERCE TO INCREASE PRODUCT SALES - Ruhiat Susanto; Vinto Rizalfi; Vanna Sok; Omar Khan (Journal of Computer Science Advancements, 2025)
The rapid development of e-commerce has led businesses to adopt innovative technologies to enhance customer engagement and increase product sales. Augmented reality (AR) has emerged as a transformative tool that allows consumers to visualize products in real-world settings, bridging the gap between physical and digital shopping experiences. This research explores the application of AR in e-commerce and its effectiveness in driving product sales by enhancing customer interaction and confidence in purchasing decisions. The study employs a mixed-method approach, combining quantitative surveys of 300 e-commerce users with qualitative interviews of 10 industry experts. The survey measured user engagement, purchasing intent, and satisfaction with AR-enhanced shopping experiences. Expert interviews provided insights into AR implementation strategies and its impact on sales performance. The findings indicate that AR significantly improves product visualization, leading to a 25% increase in customer engagement and a 30% boost in sales conversions. Consumers reported higher confidence in their purchases when using AR features, citing improved understanding of product dimensions, colors, and functionality. However, challenges such as high implementation costs and technical complexity were identified as barriers to widespread adoption. The study concludes that AR is a valuable tool for e-commerce businesses aiming to increase sales by enhancing the customer experience. Addressing challenges such as cost and accessibility will be critical for maximizing AR’s potential. Future research should explore the integration of AR with other emerging technologies to further optimize its impact on e-commerce performance.